A revision of Pseudopleonexes Conlan, 1982 (Crustacea: Amphipoda: Ampithoidae) with description of three new species from Australia - Peart, Rachael A. (Zootaxa, 2006)
Pseudopleonexes is a small genus of ampithoid amphipods previously known from only two southern hemisphere species, P. lessoniae (Hurley, 1954) and P. sheardi Just, 2002. Pseudopleonexes is revised based on type material and other collections from around Australia. Diagnoses and a key to the species are provided. Three new southern Australian species are described: P. burney sp. nov., P. justi sp. nov. and P. nexis sp. nov.